Automated Optical Surface Strain Measurement System to Determine the Transfer Length in Pretensioned Concrete Railroad Ties - Beck, B. Terry; Peterman, Robert J.; Wu, Chih-Hang (Rural Railroad Safety Center, Kansas State University., 2021)
This report documents the advances that have been made to determine the transfer length of pretensioned concrete railroad ties using non-contact surface displacement measurements by digital image correlation. The work has culminated with two fully-functional devices that address specific needs of the industry. The first device utilizes a multi-camera method for measuring the surface strain profile on a railroad tie and determining the associated transfer length to within +/- 1.5 in. with as few as 5 independent measurements of surface strain. The work represents a practical step towards the continuous monitoring of in-plant prestressed railroad tie production, using transfer length as a quality control parameter. The second device is capable of making measurements of strain in a real-time continuously scanning/traversing (CST) manner over the entire distance range of interest on the tie associated with transfer-length development. It was shown to be capable of a strain measurement resolution of nominally about ± 20 microstrain, at traversing speeds of up to several inches per second.
Keywords: Railroad Ties; Prestressed Concrete; Transfer Length; Transmission Length; Laser-Speckle; LSI